A systematic review of preclinical in vivo testing of 3D printed porous Ti6Al4V for orthopedic applications, part I: Animal models and bone ingrowth outcome measures. Issue 10 (22nd January 2021) - Spece, Hannah; Basgul, Cemile; Andrews, Caleb E.; MacDonald, Daniel W.; Taheri, Mitra L.; Kurtz, Steven M.
Abstract: For Ti6Al4V orthopedic and spinal implants, osseointegration is often achieved using complex porous geometries created via additive manufacturing (AM). While AM porous titanium (pTi) has shown clinical success, concerns regarding metallic implants have spurred interest in alternative AM biomaterials for osseointegration. Insights regarding the evaluation of these new materials may be supported by better understanding the role of preclinical testing for AM pTi. We therefore asked: (a) What animal models have been most commonly used to evaluate AM porous Ti6Al4V for orthopedic bone ingrowth; (b) What were the primary reported quantitative outcome measures for these models; and (c) What were the bone ingrowth outcomes associated with the most frequently used models? We performed a systematic literature search and identified 58 articles meeting our inclusion criteria. We found that AM pTi was evaluated most often using rabbit and sheep femoral condyle defect (FCD) models. Additional ingrowth models including transcortical and segmental defects, spinal fusions, and calvarial defects were also used with various animals based on the study goals. Quantitative outcome measures determined via histomorphometry including ''bone ingrowth'' (range: 3.92–53.4% for rabbit/sheep FCD) and bone‐implant contact (range: 9.9–59.7% for rabbit/sheep FCD) were the most common. Studies also used 3D imaging to report outcomes such as bone volume fraction (BV/TV, range: 4.4–61.1% for rabbit/sheep FCD), and push‐out testing for outcomes such as maximum removal force (range: 46.6–3092 N for rabbit/sheep FCD). Though there were many commonalities among the study methods, we also found significant heterogeneity in the outcome terms and definitions. The considerable diversity in testing and reporting may no longer be necessary considering the reported success of AM pTi across all model types and the ample literature supporting the rabbit and sheep as suitable small and large animal models, respectively. Ultimately, more standardized animal models and reporting of bone ingrowth for porous AM materials will be useful for future studies.